Knowledge and associated factors towards trachoma in rural Lemo district, Southern Ethiopia, 2021 - Mikias Mered Tilahun; Biruk Lelisa Eticha; Mulunesh Girma Shobiso; Merkineh Markos Lorato (Taylor & Francis Group, 2024)
AbstractIntroduction Trachoma is one of the Neglected Tropical diseases and the world's leading infectious cause of preventable blindness. This preventable blindness is mainly reduced by preventive measures affiliated with pre-existing knowledge about the disease's nature, transmission, and prevention strategies. The extracted result will be an asset for integrated future intervention, which boosts knowledge of the community, and finally, put a cornerstone in reducing the burden of the disease.Methods A community-based cross-sectional study in the rural Lemo district of South Ethiopia covering 552 households was conducted from 1st July-30th July 2021. We used a multistage sampling technique. Seven kebeles were selected using a simple random sampling method. Then, a systematic random sampling procedure with a five-interval size was applied to select the household.Our study assessed the association between the outcome variable and explanatory variables using binary and multivariate logistic regressions. The adjusted odds ratio was calculated and variables with a p-value below 0.05 at the 95% confidence interval were considered statistically significant.Results The study found that 58.5% (95% CI: 54.2-62.9%) of participants had good knowledge regarding trachoma. Having good attitude towards trachoma (AOR: 4.68, 95% CI: 3.09-7.10), and receiving health education (AOR: 3.12, 95% CI: 2.04-4.77), were significantly associated with good knowledge of trachoma.Conclusion Of the study participants, 58.5% had good knowledge towards trachoma. Health education and good attitude were variables associated with good knowledge of trachoma. It is advisable to take action to make people aware of trachoma through health education about the disease's nature, transmission, and prevention strategies.